Technology, Institutions and Labor Manufacturing Automobiles in Argentina and Turkey - Apaydin, Fulya (International Political Economy Series,, 2018)
In this book Fulya Apaydin argues that labor responses to dramatic technological change are influenced by the political institutions of the Global South more than any other factor. In addressing vocational education programs - which are highly relevant in understanding how labor unrest is governed in developing settings - she makes two important contributions. Firstly, she offers a new theoretical framework to understand labor mobilization and de-mobilization patterns, rethinking vocational education as a key transmission belt for manufacturing labor consent. Secondly, she provides a systematic comparison of skill formation schemes and their implications on labor mobilization in federal and unitary systems. With a focus on Argentina and Turkey, two case studies are provided in which technology has provoked differing levels of strikes, walkouts and extended protest. Fulya Apaydin is Assistant Professor at Institut Barcelona d'Estudis Internacionals, Spain. Her research focuses on comparative political economy and development.